The Ruling of Cryptocurrency According to The Indonesian Council Of Scholars(MUI) and The Indonesian Commodity Futures Trading Regulatory Agency (BAPPEBTI) - Muhammad Hafidz Muyassar; Imam Alfiannor; Miftah Faridh (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT Cryptocurrency is a form of currency that does not exist physically in the real world but only in the digital realm as data, which is bound by a hash as proof of its validity. The emergence of cryptocurrencies, especially those with high market value worldwide, has sparked debates and controversies regarding their legal status as currency or commodities in Indonesia. This paper aims to explore the conceptions of cryptocurrency according to the Indonesian Council of Scholars and the Indonesian Commodity Futures Trading Regulatory Agency (BAPPEBTI). The study adopts a normative and descriptive analytical approach in the form of a comparative study. This paper relied on two primary sources: 1) the Seventh Edict of the Indonesian Council of Scholars, which discusses cryptocurrency, issued by the Secretariat of the Fatwa Commission of the Indonesian Council of Scholars, and 2) a digital leaflet containing regulations and explanations regarding cryptocurrency regulations in Indonesia, issued by BAPPEBTI. Based on the methodology used, the research findings are as follows: First, according to the Indonesian Council of Scholars, the use of cryptocurrency as currency or commodities is deemed invalid and prohibited due to its involvement in gharar (excessive uncertainty), dharar (potential harm), and its conflict with the law that mandates the use of the Indonesian Rupiah as the official currency within the territory of the Republic of Indonesia. Second, BAPPEBTI allows the trading of cryptocurrencies that have utility as assets or commodities in Indonesia, provided they meet the requirements set by BAPPEBTI. Keywords: Crypto, Law, MUI, BAPPEBTI ABSTRAK Cryptocurrency adalah mata uang yang tidak memiliki fisik di dunia nyata dan hanya terdapat di dunia maya dalam bentuk data yang terikat dengan hash sebagai bukti validitasnya. Kemunculan cryptocurrency khususnya yang memiliki nilai jual tinggi di dunia, menimbulkan pro dan kontra berkaitan dengan hukumnya sebagai mata uang atau komoditi di Indonesia. Penelitian ini bertujuan untuk mengetahui konsepsi cryptocurrency menurut majelis ulama Indonesia dan BAPPEBTI. Penelitian ini adalah penelitian normatif bersifat deskriptif analitis yang berupa studi komparatif. Peneliti menggunakan dua sumber rujukan utama, yaitu 1) Edaran hasil Ijtima’ ketujuh Majelis Ulama Indonesia berkaitan tentang cryptocurrency oleh Sekretariat Komisi Fatwa Majelis Ulama Indonesia dan 2) Leaflet digital yang memuat peraturan dan penjelasan berkaitan dengan regulasi cryptocurrency di Indonesia yang diedarkan BAPPEBTI. Berdasarkan metode yang digunakan diperoleh hasil penelitian sebagai berikut: Pertama, menurut MUI penggunaan cryptocurrency atau kripto sebagai mata uang dan komoditi tidak sah dan hukumnya haram karena mengandung gharar, dharar dan bertentangan dengan Undang-Undang yang mewajibkan penggunaan Rupiah sebagai mata uang di wilayah NKRI. Kedua, menurut BAPPEBTI kripto yang memiliki utilitas boleh diperdagangkan sebagai aset atau komoditi di Indonesia selama memenuhi persyaratan yang telah ditetapkan oleh BAPPEBTI. Kata Kunci: Crypto, Hukum, MUI, BAPPEBTI